Perubahan Sosial Masyarakat Pasca Pengalihfungsian Lahan Sawah menjadi Lahan Perikanan: Di Desa Talun Kecamatan Kayen Kabupaten Pati - Juwita Hidayah; Abdul Malik (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2021)
This study aims to describe the social changes that occur in the Talun village community, the dynamics of the community's learning process during the land conversion process and the impact it causes. This study uses a qualitative approach with research subjects including the head of POKDAKAN Mina Sejahtera, the head of the culinary field, the head of the fishing service sector, the village secretary, and community leaders. The data validity technique uses data triangulation, while data analysis techniques include data collection, data reduction, data presentation and conclusions. The results showed that the social changes that occurred in the Talun village community were influenced by internal factors and external factors. The social changes of the Talun village community are included in the immanent changes and changes occur at the micro, intermediate, and macro levels. The social changes of the Talun village community include a structural dimension; cultural dimension; and interactional dimensions. The community learning process is through direct practice (learning by doing), group discussions and counseling. The positive impacts include: changes in the social status of the community; the preservation of cultural values; community income increases; increasing community participation in village politics; the people of Talun village have progressed in thinking. While the negative impact caused is social deviation in the form of alcoholic drinks brought in by visitors. Keywords: Community, Social Changes, Learning Process